2019
DOI: 10.1007/s10815-019-01456-3
|View full text |Cite
|
Sign up to set email alerts
|

Maternal body mass index affects embryo morphokinetics: a time-lapse study

Abstract: Purpose To assess the effect of body mass index (BMI) on morphokinetic parameters of human embryos evaluated with timelapse technology during in vitro culture. Methods A retrospective analysis of ART cycles utilizing time-lapse technology was undertaken to assess the potential impact of maternal BMI on morphokinetic and static morphological parameters of embryo development. The cohort of patients was divided into four groups: 593 embryos from 128 underweight women in group A; 5248 embryos from 1107 normal weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 59 publications
(80 reference statements)
0
24
1
Order By: Relevance
“…In contrast, a recent study including 1528 patients reported that t5 was longer in overweight women and t5 with t8 was longer in obese compared to non-obese patients. 59 Conversely, BMI was not noted to affect embryo development timing points in an analysis performed retrospectively on 89 patients. 60 …”
Section: Confounding Factorsmentioning
confidence: 89%
“…In contrast, a recent study including 1528 patients reported that t5 was longer in overweight women and t5 with t8 was longer in obese compared to non-obese patients. 59 Conversely, BMI was not noted to affect embryo development timing points in an analysis performed retrospectively on 89 patients. 60 …”
Section: Confounding Factorsmentioning
confidence: 89%
“…However, some scholars suggested that the BMI had no effect on the embryo morphokinetic parameters and embryonic development [21] . Bartolacci et al elucidated the correlation between the BMI and the embryo morphokinetic parameters using the time-lapse monitoring system and found that the embryo development in overweight or obese females was slower (t5 and t8 were prolonged), and these morphokinetic parameters may be used to improve the selection of the high-quality embryos [22] . Therefore, the present study further analyzed the participants with different BMI and found that the Day 3 high-quality embryo ratio and the blastocyst formation rate were not statistically different between participants with different BMI (P > 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we observed similar embryo morphokinetic parameters between the two study groups, but a significantly higher proportion of embryos displaying an optimal cleavage range in the very early stages of embryo development (t2 and t3) was observed in the MI + ALA + FA group compared to the FA-only group, revealing a potential, although limited, positive impact on embryo kinetics. Interestingly enough, it was previously observed that embryo morphokinetics at the cleavage stage are significantly slower in obese compared with normal-weight women [ 61 ], and that embryo development from hyperandrogenic PCOS women is significantly delayed at early stages compared with embryos from non-PCOS, regularly cycling women [ 62 ]. Taken together, these data reveal that causative factor for subfertility in overweight/obese or PCOS women may be related, at least in part, to the developmental timing of pre-implantation embryos.…”
Section: Discussionmentioning
confidence: 99%